The humanities scholars in the «non-humanitarian» world (the status of social sciences and humanities in contemporary Russia) - D G Podvoisky (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2009)
The axis of the publication is the endeavor involving the description of the situation pertaining to the status of social sciences and humanities in the contemporary Russian society. The author challenges the reader to the examination of the issue of the attitude to the bearers of «humanities scholarship» within the public consciousness of various epochs, the status of humanities scholars in the specific social and historical contexts enduring persistent transformations. The reasons for the opposition between the cultural pattern «pertaining specifically to the humanities» and the «instrumental and technocratic» one giving rise to (legitimizing) contrasting modes of world outlook and social practice strategies are highlighted.